2020
DOI: 10.1002/anie.202005627
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐Controlled Assembly of Polyoxotungstate‐Based Coordination Networks

Abstract: The Preyssler polyoxoanion, [NaP5W30O110]14− ({P5W30}), is used as a platform for evaluating the role of nonbridging cations in the formation of transition‐metal‐bridged polyoxometalate (POM) coordination frameworks. Specifically, the assembly architecture of Co2+‐bridged frameworks is shown to be dependent on the identity and amount of alkali or alkaline‐earth cations present during crystallization. The inclusion of Li+, Na+, K+, Mg2+, or Ca2+ in the framework synthesis is used to selectively synthesize five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 71 publications
(83 reference statements)
1
23
0
2
Order By: Relevance
“…In a further recent study, Schimpf and her team discovered that the competition between K + and Co 2+ for binding to {P 5 W 30 } dictates the formation of the framework. [ 31 ] Their findings provide a deep insight into the factors that govern the formation of metal‐bridged POM‐based porous networks.…”
Section: Pomzites: Pom‐based Frameworkmentioning
confidence: 99%
“…In a further recent study, Schimpf and her team discovered that the competition between K + and Co 2+ for binding to {P 5 W 30 } dictates the formation of the framework. [ 31 ] Their findings provide a deep insight into the factors that govern the formation of metal‐bridged POM‐based porous networks.…”
Section: Pomzites: Pom‐based Frameworkmentioning
confidence: 99%
“…Polyoxometalates (POMs), an effective electronic transmission medium, have the advantages of simple synthesis, lowcost, redox reversibility and excellent stability. [31][32][33][34][35][36][37][38] In the past ten years, our research team has introduced POMs into dyesensitized solar cells (DSSCs) and proved that POMs are a class of good electronic transmission medium that can store and export electrons quickly. [39][40][41][42][43][44][45][46][47] In addition, we also applied POMs to the electrode materials of the piezoelectric nanogenerator (PENG), a flexible transparent device which can convert mechanical energy into electricity effectively and further confirmed that POMs as good electron transport medium can be used in energy conversion devices.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs), an effective electronic transmission medium, have the advantages of simple synthesis, low‐cost, redox reversibility and excellent stability [31–38] . In the past ten years, our research team has introduced POMs into dye‐sensitized solar cells (DSSCs) and proved that POMs are a class of good electronic transmission medium that can store and export electrons quickly [39–47] .…”
Section: Introductionmentioning
confidence: 99%
“…However, with the addition of heterometals (other transition metals, p‐block metals, lanthanides and actinides), many inorganic frameworks have been isolated (i.e. [5–10]). With the addition of a heterometal and an organic ditopic linker, POM‐based MOFs can be isolated [5, 11–14] …”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) are anionic metal-oxo clusters, characteristic of early d 0 transition metals including V V ,N b V , Ta V ,M o VI and W VI .T hey are terminated by multiply bonded oxo groups,w hich generally prevents the formation of frameworks.H owever,w ith the addition of heterometals (other transition metals,p -block metals,l anthanides and actinides), many inorganic frameworks have been isolated (i.e. [5][6][7][8][9][10]). With the addition of ah eterometal and an organic ditopic linker,P OM-based MOFs can be isolated.…”
Section: Introductionmentioning
confidence: 99%